1996
DOI: 10.2169/internalmedicine.35.611
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Anxiety before and after Lung Cancer Chemotherapy: Relationship to Patient's Personality.

Abstract: The purpose of the study was to assess the quality of life (QOL)and anxiety in 50 inpatients with primary lung cancer and examine the influence of their personalities on the QOLassessment. We used a psychological personality test to evaluate the patient's personality, then followed the course of QOLand anxiety before and after chemotherapy. To measure QOL, we used Holmes's QOL checklist, and the State-Trait Anxiety Inventory was adopted to estimate the patient's anxiety. Eighty courses of chemotherapy were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…According to the predominant view, marked environmental change may influence the egogram. 29 Therefore, one could conceive that the results of the current study solely reflect the relation between the egogram and the physical state of the subject or the extent of his/her disease. However, the FC and AC scores among the three groups of patients with Stage I–IIIA lung carcinoma, Stage IIIB or Stage IV lung carcinoma, and those patients with no malignant lesions did not differ significantly.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to the predominant view, marked environmental change may influence the egogram. 29 Therefore, one could conceive that the results of the current study solely reflect the relation between the egogram and the physical state of the subject or the extent of his/her disease. However, the FC and AC scores among the three groups of patients with Stage I–IIIA lung carcinoma, Stage IIIB or Stage IV lung carcinoma, and those patients with no malignant lesions did not differ significantly.…”
Section: Discussionmentioning
confidence: 91%
“…However, the FC and AC scores among the three groups of patients with Stage I–IIIA lung carcinoma, Stage IIIB or Stage IV lung carcinoma, and those patients with no malignant lesions did not differ significantly. Nakada et al 29 reported that the score of the physical quality of life (the degree of tiredness, pain, appetite, etc.) was not correlated markedly with any category of the TEG among their lung carcinoma patients with an ECOG performance status of 0–3.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to survey the patients' personalities in order to grasp their QOL accurately (Nakada, 1996).…”
Section: Role Of Personality and Coping Stylesmentioning
confidence: 99%